Born to move: a review on the impact of physical exercise on brain health and the evidence from human controlled trials - Camila Vorkapic; Silvânia Leal; Heloisa Alves; Michael Douglas; André Britto; Estélio Henrique Martin Dantas (Arquivos de Neuro-Psiquiatria)
Abstract Background: Physical exercise has been found to impact neurophysiological and structural aspects of the human brain. However, most research has used animal models, which yields much confusion regarding the real effects of exercise on the human brain, as well as the underlying mechanisms. Objective: To present an update on the impact of physical exercise on brain health; and to review and analyze the evidence exclusively from human randomized controlled studies from the last six years. Methods: A search of the literature search was conducted using the MEDLINE (via PubMed), EMBASE, Web of Science and PsycINFO databases for all randomized controlled trials published between January 2014 and January 2020. Results: Twenty-four human controlled trials that observed the relationship between exercise and structural or neurochemical changes were reviewed. Conclusions: Even though this review found that physical exercise improves brain plasticity in humans, particularly through changes in brain-derived neurotrophic factor (BDNF), functional connectivity, basal ganglia and the hippocampus, many unanswered questions remain. Given the recent advances on this subject and its therapeutic potential for the general population, it is hoped that this review and future research correlating molecular, psychological and image data may help elucidate the mechanisms through which physical exercise improves brain health.